A THERMODYNAMIC MODEL FOR CALCULATING METHANE SOLUBILITY, DENSITY AND GAS PHASE COMPOSITION OF METHANE-BEARING AQUEOUS FLUIDS FROM 273 TO 523 K AND FROM 1 TO 2000 BAR - Duan Z.; Mao S. (My University, 2006)
A thermodynamic model is presented to calculate methane solubility, liquid phase density and gas phase composition of the H2O-CH4 and H2O-CH4-NaCl systems from 273 to 523 K (possibly up to 573 K), from 1 to 2000 bar and from 0 to 6 mol kg-1 of NaCl with experimental accuracy. By a more strict theoretical approach and using updated experimental data, this model made substantial improvements over previous models: (1) the accuracy of methane solubility in pure water in the temperature range between 273 and 283 K is increased from about 10% to about 5%, but confirms the accuracy of the Duan model [Duan Z., Moller N., Weare J.H., 1992a. Prediction of methane solubilities in natural waters to high ionic strength from 0 to 250 °C and from 0 to 1600 bar. Geochim. Cosmochim. Acta 56, 1451-1460] above 283 K up to 2000 bar; (2) the accuracy of methane solubility in the NaCl aqueous solutions is increased from >12% to about 6% on average from 273 K and 1 bar to 523 K and 2000 bar; (3) this model is able to calculate water content in the gas phase and liquid phase density, which cannot be calculated by previous models; and (4) it covers a wider range of temperature and pressure space. With a simple approach, this model is extended to predict CH4 solubility in other aqueous salt solutions containing Na+, K+, Mg2+, Ca2+, Cl- and SO42 -, such as seawater and geothermal brines, with excellent accuracy. This model is also able to calculate homogenization pressure of fluid inclusions (CH4-H2O-NaCl) and CH4 solubility in water at gas-liquid-hydrate phase equilibrium. A computer code is developed for this model and can be downloaded from the website: www.geochem-model.org/programs.htm. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHEMICAL COMPOSITION; DENSITY; METHANE; SOLUBILITY; THERMODYNAMICS